Evaluation of antagonism and lytic enzymes production by Trichoderma species as potential biocontrol agents against Rigidoporus microporus - Go, Wen Ze; H'ng, Paik San; Wong, Mui Yun (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Species of the genus Trichoderma are well known as the biocontrol against many plants diseases. Adoption of biological control methods as an alternative disease control measure has become a top priority these days due to the frequent use of agrochemicals that lead to environmental pollution and development of chemical resistance. A total of four Trichoderma species namely, T. koningiopsis (HT001), T. spirale (HT009), T. asperellum (ST011) and T. reesei (ST013) were isolated from rhizosphere soils of healthy and symptomatic tree area to test for their ability to inhibit the white root rot pathogen, Rigidoporus microporus in rubber tree. The strain with high antagonistic potential was determined mainly by plate assay method on each of the respective solid media. Among all, T. asperellum revealed a significant high antagonistic ability against R. microporus as compared to other strains of Trichoderma on the direct confrontation plate assay with the percentage of inhibition recorded at 93.02%. Besides that, the production of chitinase and cellulase enzymes were notable from the plate assay of T. asperellum with the formation of purple colour zone on chitinase detection plate and yellow-opaque halo zone on the cellulase detection plate. The strain was also able to produce β-1,3-glucanase in the culture medium supplied with chitin as a carbon source. These enzymes are believed to facilitate the cell wall-degradation process during the mycoparasitic activity. The above ability possessed by T. asperellum suggests that it a best candidate for the biocontrol against white root rot pathogen, R. microporus.